Psychosocial correlates of road crashes in Ibadan, Nigeria (2010)
The objectives of this study were to investigate factors that influence driving behaviour in the city of Ibadan, ascertain some of the psychosocial factors that influence road crashes in Ibadan, and attempt proffering suggestions about dealing with the identified driving problems. The study employed a correlational design. It examined psychosocial factors (such as drunken driving, impressionistic/self-regulated driving behavior, disobeying traffic laws, excessive speeding, anxiety, aggressiveness, level of education, gender and indulgence in distractive activity) that relate to road crashes. The aim was to review self-regulation of driving as a viable means of achieving safe and efficient driving among drivers. Three hundred and sixty two randomly or purposely sampled drivers participated in the study that employed thematic analyses and correlations as analysis tools. The principal finding of the study was that psychosocial factors such as drunken driving, road rage, and engaging in distractive activities while driving correlated significantly with road crashes. Discussions dwelt on the need for drivers to imbibe self-regulated driving culture.